Determining the Maternal Risk Factors Contributing to the Birth of Low Birth Weight Newborn: A Case-Control Study - Priya Rani, Batool Hassan, Mahtab Memon, Oam Parkash, Naila Bai, Faiqa Hassan, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim:To determine the maternal risk factors contributing to the birth of low birth weight newborn Study design: A case-control study Place and Duration:This study was conducted at ChildLife Foundation (CLF), Paediatric Emergency NICH Karachi Pakistan from August 2021 to January 2022. Methodology:A total of 920 mothers were included in the study that delivered the baby during the mentioned time frame, out of which 460 were cases and 460 controlled mothers for the comparative analysis of risk factors. All the newborns weighing less than 2500 grams of weight were considered as respective cases for the study. Newborns that weight more than 2500 grams were included in the control groups Results:The mean weight of newborn cases was 2.07 ± 0.45 kilograms and 3.14 ± 0.36 kilograms in the newborn control group. However, the mean gestational age of the cases was 37.2 ± 1.48, and the control was 38.3 ± 1.23 weeks. Whereas mothers of 37.2% of cases and 38.7% of control had no education background, 76% of cases had low HB levels, and 68.7% of cases had less than 24 months of the birth interval were relatedto low birth weight. There was no direct associationbetweenmaternal hypertension and low birth weight among newborns observed in the present study. Conclusion:The present study concluded that maternal low HB levels, poor socioeconomic status, low BMI, poor educational background and close birth spacing have a strong association with LBW among newborns. The country's child and maternal health care services should be prioritized to address these issues.